Debunking Immigration Myths: A Review Essay of Streets of Gold: America’s Untold Story of Immigrant Success - Tabellini, Marco (Journal of Economic Literature, 2024)
This essay reviews Streets of Gold: America’s Untold Story of Immigrant Success by Ran Abramitzky and Leah Boustan. This elegantly written book, whih is a must-read for anyone interested in the topic of immigration, walks the reader through a history of US immigration, examining patterns of immigrant assimilation from the mid-nineteenth century to today. The book challenges two myths about US immigration. First, it shows that historical European immigrants did not always arrive poor and quickly climb the economic and social ladder. Second, it documents that the pace of immigrant assimilation today resembles that prevailing at the turn of the twentieth century. (JEL J15, J18, K37, N31, N32, Z13)